ALTERNATIF PENGGUNAAN BATU PUTIH LOKAL SEBAGAI BAHAN PERKERASAN JALAN - NGITA, PASKALIS; Widodo, Esti (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Hard coat function to accept and propagate traffic burden without generating damage meaning at construction walke itself. hard Construction materials of road; street that is limber ossifying (pavement flexibel), and stiff ossifying (pavement rigid) aimed at the effort exploiting of local material and adapted for by the condition of area where ossification construction will be executed. In this research use methodologies examination of marshall to analyse the nature of from gratuity cavity in mixture (VIM), gratuity cavity loaded asphalt (VFB), gratuity cavity among aggregate mineral (VMA), stability, Flow and Marshall Quatient. Making of object test counted 6, 3 object test for the mixture of asphalt using white stone and 3 object test for the mixture of asphalt using black stone with rate pave 5,5%. This research is done in Technique Civil University laboratory of Tribhuwana Tunggadewi. Step Execution cover inspection of asphalt of AC 60 / 70, inspection of harsh aggregate (black stone and white stone), inspection of smooth aggregate (black stone and white stone), inspection of filler, making of object test and examination of Marshall. Harsh aggregate which used by stone break of the size aggregate which is filter of No.8 (2,36 mm), smooth aggregate geting away filter of No.8 (2,36 mm) filter of No. 200 (0,075 mm), while for the materials of filler which get away filter of No. 200 (0,075 mm). Of the aggregate combination obtained by harsh aggregate faction equal to 52,5%, smooth aggregate faction equal to 40,5%, and filler equal to 7,0%. Result of characteristic performance test of Marshall: Stability average value (black stone aggregate 605,967 kg white stone aggregate 251,833 kg), average value of Flow (black stone aggregate 2,65 mm white stone aggregate 2,74 mm), average value of VIM (black stone aggregate 15,033% and white stone aggregate 20,277%), average value of VMA (black stone aggregate 25,687% and white stone aggregate 30,137%), average value of VFB (black stone aggregate 41,547% and white stone aggregate 32,728%), and average value of Marshall Quotient (black stone aggregate 226,598 kg/mm and white stone aggregate 84,794 kg/mm). Keywords : Marshall, White Stone, Stability, Flow, Marshall Quotient. ABSTRAK Lapisan perkerasan berfungsi untuk menerima dan menyebarkan beban lalu lintas tanpa menimbulkan kerusakan yang berarti pada konstruksi jalan itu sendiri. Bahan konstruksi perkerasan jalan yaitu perkerasan lentur (flexibel pavement) , dan perkerasan kaku (rigid pavement) diarahkan pada usaha pemanfaatan material setempat dan disesuaikan dengan kondisi daerah dimana konstruksi pengerasan akan dilaksanakan. Dalam penelitian ini menggunakan metodologi pengujian marshall untuk menganalisa sifat-sifat dari persen rongga dalam campuran (VIM), persen rongga terisi aspal (VFB), persen rongga diantara mineral agregat (VMA), stabilitas (Stability), kelelehan (Flow) dan Marshall Quatient . Pembuatan benda uji sebanyak 6 buah, 3 benda uji untuk campuran aspal yang menggunakan batu putih dan 3 benda uji untuk campuran aspal yang menggunakan batu hitam (batu kali/batu gunung) dengan kadar aspal 5,5%. Penelitian ini dilakukan di laboratorium Teknik Sipil Universitas Tribhuwana Tunggadewi, Malang. Tahapan pelaksanaan meliputi pemeriksaan aspal AC 60/70, pemeriksaan agregat kasar (batu hitam dan batu putih), pemeriksaan agregat halus (batu hitam dan batu putih), pemeriksaan filler, pembuatan benda uji dan pengujian Marshall. Agregat kasar yang digunakan batu pecah dengan ukuran agregat yang tertahan saringan No.8 (2,36 mm), agregat halus yang lolos saringan No.8 (2,36 mm) tertahan saringan No. 200 (0,075 mm), sedangkan untuk bahan pengisi yang lolos saringan No. 200 (0,075 mm). Dari kombinasi agregat tersebut diperoleh fraksi agregat kasar sebesar 52,5%, fraksi agregat halus sebesar 40,5%, dan filler sebesar 7,0%. Hasil uji kinerja karakteristik Marshall didapat: nilai rerata Stabilitas (agregat batu hitam 605,967 kg dan agregat batu putih 251,833 kg), nilai rerata Flow (agregat batu hitam 2,65 mm dan agregat batu putih 2,74 mm), nilai rerata VIM (agregat batu hitam 15,033% dan agregat batu putih 20,277%), nilai rerata VMA(agregat batu hitam 25,687% dan agregat batu putih 30,137%), nilai rerata VFB (agregat batu hitam 41,547% dan agregat batu putih 32,728%), dan nilai rerata Marshall Quotient (agregat batu hitam 226,598 kg/mm dan agregat batu putih 84,794 kg/mm). Kata kunci : Marshall, Batu Putih, Stabilitas, Flow, Marshall Quotient.